Outcome after 8 years of a modified conservative treatment experience in keratocystic odontogenic tumor in 5 patients (2017)
The keratocystic odontogenic tumor (KCOT) according to WHO classification comprises approximately 12% of all tumors of the jaw. The pathognomonic microscopic findings are the parakeratin at the superficial layer. Their clinical and radiographic presentation is variable, showing different degrees of aggressive behavior and recurrences. We present a retrospective study with a modified conservative approach for the treatment of the KCOT. Five patients between 16 and 23 years old were treated in 2009. These presented radiologic features suggestive of KCOT such as unilocular lesions in the mandible. The diagnosis was confirmed by incisional biopsy and histopathological study of every lesion. The treatment performed was: Carnoy's solution by 5 minutes without chloroform and decompression with plastic stents from 7 to 11 months, switching the position of the stents once bone formation was evident, Carnoy's again for 3 minutes, enucleation, peripheral ostectomy, and concomitant xenograft. All the patients underwent simultaneous xenograft reconstruction after enucleation. Recurrence was negative after 8 years of follow up. No patient showed infection or fracture, only 1 reported discomfort with the stent. The modified treatment in our study suggests that this protocol so far has a low recurrence rate. The commitment of the patient is important for the long-term follow up and treatment. © 2017 The Author(s)